Schiff base modified silane / polyurethane antifouling coating as well as preparation method and application thereof
By combining Schiff base modified silane with polyurethane, an antifouling coating with good static antifouling and excellent mechanical properties in seawater was prepared, which solved the problem of poor antifouling performance and poor mechanical properties of antifouling coating in seawater in the prior art, and achieved a longer service life and better antifouling effect.
Patent Information
- Application Number
- CN202411773872.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-28
AI Technical Summary
The existing marine anti-fouling coatings have poor static anti-fouling performance in seawater and have poor mechanical properties, making it difficult to effectively extend their service life.
The antifouling coating combined with Schiff base modified silane and polyurethane is used to prepare Schiff base modified silane monomer by dehydration reaction of aldehyde substances and aminosilanes, and react with materials such as polyether diol and diisocyanate to form polymer B and then coat it on the substrate to cure.
The coating exhibits good static anti-fouling effect in seawater, enhancing its resistance to marine polluted organisms, and at the same time it has excellent mechanical properties and effective dirt release ability, extending its service life.
Smart Images

Figure BDA0005170927410000051
Abstract
Description
Technical Field
[0001] The invention relates to the field of marine antifouling coatings, and in particular to a Schiff base modified silane / polyurethane antifouling coating and a preparation method and application thereof. Background Art
[0002] Marine fouling is a common problem that accompanies human marine activities and the development of marine industry. Once marine fouling attaches to the surface of artificial facilities, it will cause serious adverse effects on the substrate: the attachment of marine fouling will accelerate the corrosion of the substrate, resulting in a reduction in the strength of the artificial facility substrate or even destruction; the attachment of marine fouling will increase the deadweight of the hull and increase the roughness of the hull surface, thereby reducing the speed of the ship and accelerating the consumption of fuel; and the marine fouling attached to the hull can cause species invasion to other sea areas through the transportation of the hull, destroying the ecological balance of the local sea area. In addition, the International Maritime Organization (IMO) recently adopted new international rules and formulated a preliminary strategy to prevent the invasion of alien species.
[0003] Chinese patent document CN113698561A discloses a method for preparing a main chain degradable metal ion complexed poly Schiff base antifouling resin, which integrates two antifouling materials: metal ion antifouling and Schiff base antifouling. By changing the degree of metal ion complexation, the mechanical strength and degradation rate of the resin and coating can be adjusted over a wide range, and the antifouling effect is excellent.
[0004] Chinese patent document CN111635693A discloses an intrinsic antifouling resin and its preparation method. The intrinsic antifouling resin of the present invention integrates two antibacterial materials, functionalized polyaniline and modified Schiff base, for the first time, and designs and assembles new polyurethane molecules, which can achieve an antifouling effect of up to 48 months. It has the advantages of easy use, simple preparation, low cost, and strong antifouling effect.
[0005] The present invention starts from a different inventive concept and introduces Schiff base modified silane into polyurethane resin for the first time. The prepared coating has good mechanical properties while ensuring antifouling performance. Summary of the invention
[0006] Therefore, the purpose of the present invention is to propose a Schiff base modified silane / polyurethane antifouling coating and its preparation method and application, the Schiff base modified silane / polyurethane antifouling coating can maintain a good static antifouling effect in seawater, the coating has good mechanical properties, and effectively prolongs the service life of the coating.
[0007] The technical solutions adopted are:
[0008] A method for preparing a Schiff base modified silane / polyurethane antifouling coating of the present invention comprises the following steps:
[0009] S1. preparing a Schiff base-modified silane monomer by dehydration reaction of an aldehyde substance and an aminosilane, followed by hydrolysis;
[0010] S2. After removing water from the polyether diol, the mixture was uniformly mixed with the diisocyanate, and the mixture was cooled and refluxed at 60-80° C. under stirring to obtain a polymer A;
[0011] S3. The polymer A, the Schiff base modified silane monomer, the solvent and the dibutyltin dilaurate catalyst are uniformly mixed to obtain a polymer B by reaction;
[0012] S4. Apply polymer B on the substrate and cure it to obtain a coating.
[0013] Furthermore, in S1, the Schiff base modified silane monomer is obtained by the following preparation method, comprising the following steps:
[0014] S11. Dissolve salicylaldehyde in ethanol, referred to as solution A, and heat the solution to 80-90°C under a nitrogen atmosphere; add 3-aminopropyltriethoxysilane dropwise to solution A within 2-3 hours, and continue the reaction for 5-6 hours. Remove the ethanol from the product by a rotary evaporator to obtain a Schiff base-modified silane precursor;
[0015] S12. Add ethanol to deionized water, stir evenly on a magnetic stirrer, and slowly drop the Schiff base-modified silane precursor synthesized in step S11; wherein the mass ratio of the Schiff base-modified silane precursor, deionized water and ethanol is 1:1:6-9; add ammonia solution to adjust the pH value to 9-11, and continue stirring for 10-12 hours until the solution is transparent; after the reaction is completed, remove the ethanol with a rotary evaporator to obtain a Schiff base-modified silane monomer.
[0016] Furthermore, in S2, the diisocyanate is one or more of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexane diisocyanate and isophorone diisocyanate.
[0017] Furthermore, in S2, the polyether diol is one or more of polytetramethylene glycol, polyethylene glycol, and polypropylene glycol, and the number average molecular weight thereof is 1000-3000.
[0018] Furthermore, in S2, the mass ratio of polyether diol to diisocyanate is (2-10):1.
[0019] Furthermore, in S3, the solvent is one or more of toluene, xylene, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, ethyl acetate, acetone, acetonitrile and dichloromethane.
[0020] Furthermore, in S3, the mass ratio of the Schiff base modified silane monomer, polymer A, dibutyltin dilaurate catalyst and solvent is: (0.05-0.15):1:(0.005-0.01):(0.2-0.5).
[0021] Further, in S4, polymer B is coated on a substrate to prepare a sample, and the prepared sample is placed in an oven at 80° C. for curing for 24-72 hours.
[0022] The Schiff base modified silane / polyurethane antifouling coating of the present invention is prepared by the preparation method described in any one of the above schemes.
[0023] The present invention discloses an application of a Schiff base modified silane / polyurethane antifouling coating prepared by the preparation method described in any one of the above schemes on the surface of a ship hull.
[0024] In the above technical solution,
[0025] The present invention uses polyether diol and diisocyanate as raw materials to prepare a prepolymer, and uses Schiff base modified silane monomer as an antifouling agent to prepare a polyurethane coating. The Schiff base modified silane / polyurethane antifouling coating of the present invention not only reduces the surface energy of the coating, but also enhances the resistance to marine fouling organisms, thereby solving the problem of poor static antifouling performance of organic silicon materials. At the same time, in order to solve the problems of poor mechanical properties and low adhesion of organic silicon materials, polyurethane with excellent mechanical properties is selected as the substrate, and the synergistic effect between Schiff base modified silane and polyurethane creates excellent mechanical properties and effective fouling release ability of the coating.
[0026] In summary, compared with the prior art, the present invention has the following advantages:
[0027] 1. The present invention introduces Schiff base modified silane antifouling monomer into the field of polyurethane antifouling coating for the first time;
[0028] 2. The organosilicon component in the antifouling coating of the present invention can effectively reduce the surface energy of the coating. Seawater will wash away the fouling organisms on the coating, inhibit the adhesion of initial proteins and bacteria, and reduce the chance of large-scale fouling adhesion. At the same time, the Schiff base has the ability to eliminate fouling microorganisms when in contact with the coating surface, giving the coating static antifouling properties, thereby greatly reducing the possibility of invasion by alien species.
[0029] 3. The polyurethane in the antifouling coating of the present invention has excellent mechanical properties, which can prevent mechanical damage to the coating and improve the mechanical durability of the antifouling coating.
[0030] 4. The preparation process of antifouling coating is simple and low-cost. The Schiff base-modified silane monomer is used as a curing agent and is applicable to most polyurethane coatings, with broad prospects for industrial application. DETAILED DESCRIPTION
[0031] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary embodiments are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, and do not limit the protection scope of the present invention to these.
[0032] Example 1
[0033] The preparation method of a Schiff base modified silane / polyurethane antifouling coating of this embodiment comprises the following steps:
[0034] Step 1: Preparation of Schiff base modified silane monomer:
[0035] S11. Dissolve salicylaldehyde in ethanol, referred to as solution A, and heat the mixture to 80°C under a nitrogen atmosphere; add 3-aminopropyltriethoxysilane dropwise to solution A within 2-3 hours, and continue the reaction for 5-6 hours. Remove the ethanol from the product by a rotary evaporator to obtain a Schiff base-modified silane precursor;
[0036] S12. Add ethanol to deionized water, stir evenly on a magnetic stirrer, and slowly dropwise add the Schiff base-modified silane precursor synthesized in step S11; wherein the mass ratio of the Schiff base-modified silane precursor, deionized water and ethanol is 1:1:6; dropwise add an ammonia solution to adjust the pH value to 9-11, and continue stirring for 10-11 hours until the solution is transparent; after the reaction is completed, remove the ethanol with a rotary evaporator to obtain a Schiff base-modified silane monomer;
[0037] Step 2: Preparation of polyurethane prepolymer
[0038] 50 g of polytetramethylene ether diol was heated in a round-bottom flask at 110° C. under vacuum for 2 h to remove moisture, and then cooled to room temperature. 14.8 g of hexamethylene diisocyanate was added to a round-bottom flask equipped with a thermometer, a magnetic stirrer and a reflux condenser, and then the temperature was raised to 80° C. and reacted for 2.5 h to obtain a polyurethane prepolymer;
[0039] Step 3: Preparation of polyurethane antifouling coating
[0040] 10g of polyurethane prepolymer was weighed and added into a container, 2g of solvent and 1.5g of Schiff base modified silane were weighed and added into the polyurethane prepolymer, and 0.05g of dibutyltin dilaurate catalyst was added, and then the mixture was put into a degassing machine for stirring, degassing and vacuuming. After the reaction was completed, the product obtained was recorded as product B, and the reaction formula is shown below;
[0041]
[0042] Step 4: Spin-coat the product B on the substrate by spin coating. Place the prepared sample at room temperature for 2 hours, and heat it to 80°C for curing for 24 hours to obtain coating C;
[0043] Laboratory static diatom inhibition experiment: the sample coating size was made into 2.5cm×3.5cm, and a glass slide was selected as a blank control. The sample and the blank were immersed in the double-browed algae solution for 1 day and 3 days. After the sample was taken out, the unattached algae were removed and the algae attachment on the coating was photographed under an optical microscope. Three areas of each coating were randomly selected for photography and finally compared with the blank sample. The diatom inhibition rates were calculated to be 94.7% and 95.8% respectively.
[0044] Laboratory static antibacterial experiment: The sample coating size is made into 2.5cm×3.5cm, and a glass slide is selected as a blank control. The sample and the blank are co-cultured with the bacteria (Xiamen Pseudoalteromonas) at 28°C for 24 hours. After dilution and equal concentration, the bacterial solution is coated on the solid culture medium by the plate coating method (each sample is coated in parallel 3 times), and cultivated at 28°C for 24 hours. The plate is taken out and the number of bacteria adhering to the coating surface is determined by plate counting. The colony count method is used to calculate the number of colonies on the sample and the blank, and the antibacterial rate of the polyurethane antifouling coating on Xiamen Pseudoalteromonas is calculated to be: 95.3%.
[0045] Laboratory wear test: The wear resistance of the coating was tested by a tabletop wear tester. The turntable speed was set to 60r / min, and the cycle was 500 times. The weight loss was expressed as the difference between the coating mass before and after the experiment. The calculated mass loss was: 0.011g.
[0046] Laboratory adhesion test: The prepared polymer coating is evenly coated on the steel plate and placed in a vacuum oven for curing. A pull-out ingot is glued to the surface of the polymer coating to be tested using a quick-drying adhesive and left at room temperature for curing before being tested using a pull-out adhesion tester. The recorded value is: 5.97MPa.
[0047] Example 2
[0048] The preparation method of a Schiff base modified silane / polyurethane antifouling coating of this embodiment comprises the following steps:
[0049] Step 1: Preparation of Schiff base modified silane monomer: Same as Example 1, no further details are given.
[0050] Step 2: Preparation of polyurethane prepolymer
[0051] 60 g of polytetramethylene ether diol was heated in a round-bottom flask at 110° C. under vacuum for 2 h to remove moisture, and then cooled to room temperature. 14.8 g of hexamethylene diisocyanate was added to a round-bottom flask equipped with a thermometer, a magnetic stirrer and a reflux condenser, and then the temperature was raised to 80° C. and reacted for 2.5 h to obtain a polyurethane prepolymer;
[0052] Step 3: Preparation of polyurethane antifouling coating
[0053] Weigh 10g of polyurethane prepolymer and add it into a container, weigh 2g of solvent and 1.2g of Schiff base modified silane and add them to the polyurethane prepolymer, then add 0.05g of dibutyltin dilaurate catalyst, and then put it into a degassing machine for stirring and degassing. After the reaction is completed, the product obtained is recorded as product B, and the reaction formula is the same as Example 1.
[0054] Step 4: Spin-coat the product B on the substrate by spin coating. Place the prepared sample at room temperature for 2 hours, and heat it to 80°C for curing for 24 hours to obtain coating C;
[0055] Laboratory static diatom inhibition experiment: the sample coating size was made into 2.5cm×3.5cm, and a glass slide was selected as a blank control. The sample and the blank were immersed in the double-browed algae solution for 1 day and 3 days. After the sample was taken out, the unattached algae were removed and the algae attachment on the coating was photographed under an optical microscope. Three areas of each coating were randomly selected for photography and finally compared with the blank sample. The diatom inhibition rates were calculated to be 95.8% and 94.7% respectively.
[0056] Laboratory static antibacterial experiment: The sample coating size is made into 2.5cm×3.5cm, and a glass slide is selected as a blank control. The sample and the blank are co-cultured with the bacteria (Xiamen Pseudoalteromonas) at 28°C for 24 hours. After dilution and equal concentration, the bacterial solution is coated on the solid culture medium by the plate coating method (each sample is coated in parallel 3 times), and cultivated at 28°C for 24 hours. The plate is taken out and the number of bacteria adhering to the coating surface is determined by plate counting. The colony counting method is used to calculate the number of colonies on the sample and the blank, and the antibacterial rate of the polyurethane antifouling coating on Xiamen Pseudoalteromonas is calculated to be: 85.8%.
[0057] Laboratory wear test: The wear resistance of the coating was tested by a tabletop wear tester. The turntable speed was set to 60r / min, and the cycle was 500 times. The weight loss was expressed as the difference between the coating mass before and after the experiment. The calculated mass loss was: 0.0093g.
[0058] Laboratory adhesion test: The prepared polymer coating is evenly coated on the steel plate and placed in a vacuum oven for curing. A pull-out ingot is glued to the surface of the polymer coating to be tested using a quick-drying adhesive and left at room temperature for the glue to cure before testing using a pull-out adhesion tester. The recorded value is: 7.33MPa.
[0059] Example 3
[0060] The preparation method of a Schiff base modified silane / polyurethane antifouling coating of this embodiment comprises the following steps:
[0061] Step 1: Preparation of Schiff base modified silane monomer: Same as Example 1, no further details are given.
[0062] Step 2: Preparation of polyurethane prepolymer
[0063] 70 g of polytetrahydrofuran ether diol was heated in a round-bottom flask at 110° C. under vacuum for 2 h to remove moisture, and then cooled to room temperature. 14.8 g of hexamethylene diisocyanate was added to a round-bottom flask equipped with a thermometer, a magnetic stirrer and a reflux condenser, and then the temperature was raised to 80° C. and reacted for 2.5 h to obtain a polyurethane prepolymer;
[0064] Step 3: Preparation of polyurethane antifouling coating
[0065] 10 g of polyurethane prepolymer was weighed and added into a container, 2 g of solvent and 0.9 g of butyl Schiff base modified silane were weighed and added into the polyurethane prepolymer, and 0.05 g of dibutyltin dilaurate catalyst was added, and then the mixture was put into a degassing machine for stirring and degassing. After the reaction was completed, the product obtained was recorded as product B, and the reaction formula was the same as that in Example 1;
[0066] Step 4: Spin-coat the product B on the substrate by spin coating. Place the prepared sample at room temperature for 2 hours, and heat it to 80°C for curing for 24 hours to obtain coating C;
[0067] Laboratory static diatom inhibition experiment: the sample coating size was made into 2.5cm×3.5cm, and a glass slide was selected as a blank control. The sample and the blank were immersed in the double-browed algae solution for 1 day and 3 days. After the sample was taken out, the unattached algae were removed and the algae attachment on the coating was photographed under an optical microscope. Three areas of each coating were randomly selected for photography and finally compared with the blank sample. The diatom inhibition rates were calculated to be 94.2% and 93.1% respectively.
[0068] Laboratory static antibacterial experiment: The sample coating size is made into 2.5cm×3.5cm, and a glass slide is selected as a blank control. The sample and the blank are co-cultured with the bacteria (Xiamen Pseudoalteromonas) at 28℃ for 24h. After dilution and equal concentration, the bacterial solution is coated on the solid culture medium by the plate coating method (each sample is coated in parallel 3 times), and cultivated at 28℃ for 24h. The plate is taken out and the number of bacteria adhering to the coating surface is determined by plate counting. The colony counting method is used to calculate the number of colonies on the sample and the blank, and the antibacterial rate of the polyurethane antifouling coating on Xiamen Pseudoalteromonas is calculated to be 80.3%.
[0069] Laboratory wear test: The wear resistance of the coating was tested by a tabletop wear tester. The turntable speed was set to 60r / min, and the cycle was 500 times. The weight loss was expressed as the difference between the coating mass before and after the experiment. The calculated mass loss was: 0.0082g.
[0070] Laboratory adhesion test: The prepared polymer coating is evenly coated on the steel plate and placed in a vacuum oven for curing. A pull-out ingot is glued to the surface of the polymer coating to be tested using a quick-drying adhesive and left at room temperature for the glue to cure before testing using a pull-out adhesion tester. The recorded value is: 5.82MPa.
[0071] Example 4
[0072] The preparation method of a Schiff base modified silane / polyurethane antifouling coating of this embodiment comprises the following steps:
[0073] Step 1: Preparation of Schiff base modified silane monomer: Same as Example 1, no further details are given.
[0074] Step 2: Preparation of polyurethane prepolymer
[0075] 80 g of polytetramethylene ether diol was heated in a round-bottom flask at 110° C. under vacuum for 2 h to remove moisture, and then cooled to room temperature. 14.8 g of hexamethylene diisocyanate was added to a round-bottom flask equipped with a thermometer, a magnetic stirrer and a reflux condenser, and then the temperature was raised to 80° C. and reacted for 2.5 h to obtain a polyurethane prepolymer;
[0076] Step 3: Preparation of polyurethane antifouling coating
[0077] 10 g of polyurethane prepolymer was weighed and added into a container, 5 g of solvent and 0.7 g of Schiff base modified silane were weighed and added into the polyurethane prepolymer, and 0.05 g of dibutyltin dilaurate catalyst was added, and then the mixture was placed into a degassing machine for stirring and degassing. After the reaction was completed, the product obtained was recorded as product B, and the reaction formula was the same as that in Example 1;
[0078] Step 4: Spin-coat the product B on the substrate by spin coating. Place the prepared sample at room temperature for 2 hours, and heat it to 80°C for curing for 24 hours to obtain coating C;
[0079] Laboratory static diatom inhibition experiment: the sample coating size was made into 2.5cm×3.5cm, and a glass slide was selected as a blank control. The sample and the blank were immersed in the double-browed algae solution for 1 day and 3 days. After the sample was taken out, the unattached algae were removed and the algae attachment on the coating was photographed under an optical microscope. Three areas of each coating were randomly selected for photography and finally compared with the blank sample. The diatom inhibition rates were calculated to be 91.2% and 88.5% respectively.
[0080] Laboratory static antibacterial experiment: The sample coating size is made into 2.5cm×3.5cm, and a glass slide is selected as a blank control. The sample and the blank are co-cultured with the bacteria (Xiamen Pseudoalteromonas) at 28°C for 24 hours. After dilution and equal concentration, the bacterial solution is coated on the solid culture medium by the plate coating method (each sample is coated in parallel 3 times), and cultivated at 28°C for 24 hours. The plate is taken out and the number of bacteria adhering to the coating surface is determined by plate counting. The colony count method is used to calculate the number of colonies on the sample and the blank, and the antibacterial rate of the polyurethane antifouling coating on Xiamen Pseudoalteromonas is calculated to be: 78.5%.
[0081] Laboratory wear test: The wear resistance of the coating was tested by a tabletop wear tester. The turntable speed was set to 60r / min, and the cycle was 500 times. The weight loss was expressed as the difference between the coating mass before and after the experiment. The calculated mass loss was: 0.0072g.
[0082] Laboratory adhesion test: The prepared polymer coating is evenly coated on the steel plate and placed in a vacuum oven for curing. A pull-out ingot is glued to the surface of the polymer coating to be tested using a quick-drying adhesive and left at room temperature for the glue to cure before testing using a pull-out adhesion tester. The recorded value is: 4.83MPa.
[0083] Example 5
[0084] The preparation method of a Schiff base modified silane / polyurethane antifouling coating of this embodiment comprises the following steps:
[0085] Step 1: Preparation of Schiff base modified silane monomer: Same as Example 1, no further details are given.
[0086] Step 2: Preparation of polyurethane prepolymer
[0087] 90 g of polytetramethylene ether diol was heated in a round-bottom flask at 110° C. under vacuum for 2 h to remove moisture, and then cooled to room temperature. 14.8 g of hexamethylene diisocyanate was added to a round-bottom flask equipped with a thermometer, a magnetic stirrer and a reflux condenser, and then the temperature was raised to 80° C. and reacted for 2.5 h to obtain a polyurethane prepolymer;
[0088] Step 3: Preparation of polyurethane antifouling coating
[0089] 10 g of polyurethane prepolymer was weighed and added into a container, 2 g of solvent and 0.6 g of Schiff base modified silane were weighed and added into the polyurethane prepolymer, and 0.05 g of dibutyltin dilaurate catalyst was added, and then the mixture was put into a degassing machine for stirring and degassing. After the reaction was completed, the product obtained was recorded as product B, and the reaction formula was the same as that in Example 1;
[0090] Step 4: Spin-coat the product B on the substrate by spin coating. Place the prepared sample at room temperature for 2 hours, and heat it to 80°C for curing for 24 hours to obtain coating C;
[0091] Laboratory static diatom inhibition experiment: the sample coating size was made into 2.5cm×3.5cm, and a glass slide was selected as a blank control. The sample and the blank were immersed in the double-browed algae solution for 1 day and 3 days. After the sample was taken out, the unattached algae were removed and the algae attachment on the coating was photographed under an optical microscope. Three areas of each coating were randomly selected for photography and finally compared with the blank sample. The diatom inhibition rates were calculated to be 88.1% and 87.5% respectively.
[0092] Laboratory static antibacterial experiment: The sample coating size is made into 2.5cm×3.5cm, and a glass slide is selected as a blank control. The sample and the blank are co-cultured with the bacteria (Xiamen Pseudoalteromonas) at 28°C for 24 hours. After dilution and equal concentration, the bacterial solution is coated on the solid culture medium by the plate coating method (each sample is coated in parallel 3 times), and cultivated at 28°C for 24 hours. The plate is taken out and the number of bacteria adhering to the coating surface is determined by plate counting. The colony counting method is used to calculate the number of colonies on the sample and the blank, and the antibacterial rate of the polyurethane antifouling coating on Xiamen Pseudoalteromonas is calculated to be: 73.7%.
[0093] Laboratory wear test: The wear resistance of the coating was tested by a tabletop wear tester. The turntable speed was set to 60r / min, and the cycle was 500 times. The weight loss was expressed as the difference between the coating mass before and after the experiment. The calculated mass loss was: 0.0031g.
[0094] Laboratory adhesion test: The prepared polymer coating is evenly coated on the steel plate and placed in a vacuum oven for curing. A pull-out ingot is glued to the surface of the polymer coating to be tested using a quick-drying adhesive and left at room temperature for the glue to cure before testing using a pull-out adhesion tester. The recorded value is: 6.33MPa.
[0095] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a Schiff base modified silane / polyurethane antifouling coating, characterized in that: The following steps are involved: S1. preparing a Schiff base-modified silane monomer by dehydrating an aldehyde substance and an aminosilane, and then hydrolyzing the aldehyde substance and the aminosilane; S2. After removing water from the polyether diol, the mixture was uniformly mixed with diisocyanate, and the mixture was cooled and refluxed at 60-80° C. under stirring to obtain polymer A; S3. The polymer A, the Schiff base modified silane monomer, the solvent and the dibutyltin dilaurate catalyst are uniformly mixed to obtain a polymer B by reaction; S4. Apply polymer B on the substrate and cure it to obtain a coating.
2. The method for preparing the Schiff base modified silane / polyurethane antifouling coating according to claim 1, characterized in that: In S1, the Schiff base modified silane monomer is obtained by the following preparation method, comprising the following steps: S11. Dissolve salicylaldehyde in ethanol, referred to as solution A, and heat the solution to 80-90°C under a nitrogen atmosphere; add 3-aminopropyltriethoxysilane dropwise to solution A within 2-3 hours, and continue the reaction for 5-6 hours. Remove the ethanol from the product by a rotary evaporator to obtain a Schiff base-modified silane precursor; S12. Add ethanol to deionized water, stir evenly on a magnetic stirrer, and slowly dropwise add the Schiff base-modified silane precursor synthesized in step S11; The mass ratio of the Schiff base modified silane precursor, deionized water and ethanol is 1:1:6-9; an ammonia solution is added dropwise to adjust the pH value to 9-11, and stirring is continued for 10-12 hours until the solution is transparent; after the reaction is completed, the ethanol is removed by a rotary evaporator to obtain a Schiff base modified silane monomer.
3. The method for preparing the Schiff base modified silane / polyurethane antifouling coating according to claim 1, characterized in that: In S2, the diisocyanate is one or more of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexane diisocyanate and isophorone diisocyanate.
4. The method for preparing the Schiff base modified silane / polyurethane antifouling coating according to claim 1, characterized in that: In S2, the polyether diol is one or more of polytetramethylene glycol, polyethylene glycol, and polypropylene glycol, and the number average molecular weight thereof is 1000-3000.
5. The method for preparing the Schiff base modified silane / polyurethane antifouling coating according to claim 1, characterized in that: In S2, the mass ratio of polyether diol to diisocyanate is (2-10):
1.
6. The method for preparing the Schiff base modified silane / polyurethane antifouling coating according to claim 1, characterized in that: In S3, the solvent is one or more of toluene, xylene, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, ethyl acetate, acetone, acetonitrile and dichloromethane.
7. The method for preparing the Schiff base modified silane / polyurethane antifouling coating according to claim 1, characterized in that: In S3, the mass ratio of the Schiff base modified silane monomer, polymer A, dibutyltin dilaurate catalyst and solvent is: (0.05-0.15):1:(0.005-0.01):(0.2-0.5).
8. The method for preparing the Schiff base modified silane / polyurethane antifouling coating according to claim 1, characterized in that: In S4, polymer B is coated on a substrate to prepare a sample, and the prepared sample is placed in an oven at 80° C. for curing for 24-72 hours.
9. A Schiff base modified silane / polyurethane antifouling coating, which is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the Schiff base modified silane / polyurethane antifouling coating prepared by the preparation method according to any one of claims 1 to 8 on the surface of a ship hull.
Citation Information
Patent Citations
Intrinsic antifouling resin as well as preparation method and application thereof
CN111635693A
Main chain degradation type metal ion complexation poly-Schiff base antifouling resin, preparation method and application
CN113698561A
Polyurethane composition containing polyaldimine
US20060122352A1
Aldiminoalkylsilanes
US20080138522A1
Cycloaliphatic polyurethane composition containing cycloaliphatic dialdimines
US20100048770A1
Cited By
Super-hydrophobic corrosion-resistant coating for stainless steel and preparation method of super-hydrophobic corrosion-resistant coating
CN120623854A
A super-hydrophobic corrosion-resistant coating for stainless steel and a method for preparing the same
CN120623854B
Paper plastic removal production process based on nano plastic removal oil
CN120921837A